The "Prophetical Tenor" of Pseudo-Philo's Liber Antiquitatum Biblicarum - Bohlinger, Tavis A. (The catholic biblical quarterly, 2019)
In this article, I seek to demonstrate a previously unidentified phenomenon in Pseudo-Philo's Liber Antiquitatum Biblicarum (L.A.B.) that I call the "prophetical tenor." I argue that L.A.B. offers a more idiosyncratic reading of Israel's history than has previously been appreciated. Pseudo-Philo does not simply interject elements from the prophets piecemeal but, rather, amalgamates the Prophets with the patriarchs comprehensively. In other words, Pseudo-Philo does not read "backwards," but "vatically." In order to demonstrate the prophetical tenor of L.A.B., I present examples from three distinct categories: pre-vocalization (characters speaking words from the Prophets); character conflation (characters merged with prophetic personalities); and prophetic parlance (terminology with special significance in the Prophets). I conclude with considerations of the impact of the prophetical tenor on future readings of L.A.B. and, in particular, how the theological concerns of the author are better comprehended through a "vatical" reading of the text.